2021
DOI: 10.2139/ssrn.3905062
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Double-Fortified Salt on Anemia and Cognition: Four-Year Follow-Up Evidence from a School-Based Nutrition Intervention in India

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In contrast, the reduction in mild anemia is 6 percentage points or approximately 30%; the point estimate for moderate or severe anemia is also quite large and negative (13 percentage points) but the effects are not statistically significant. Some of the prior studies reported a similar effect size, found a reduction in anemia by 20% in India, and reported an effect size of 34.5% in Peru, while some studies were unable to find any significant impacts of DFS on anemia in India ( 13 , 14 ). The issue now seems to have settled in favor of the distribution of DFS in MDMs and the Integrated Child Development Scheme (ICDS).…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, the reduction in mild anemia is 6 percentage points or approximately 30%; the point estimate for moderate or severe anemia is also quite large and negative (13 percentage points) but the effects are not statistically significant. Some of the prior studies reported a similar effect size, found a reduction in anemia by 20% in India, and reported an effect size of 34.5% in Peru, while some studies were unable to find any significant impacts of DFS on anemia in India ( 13 , 14 ). The issue now seems to have settled in favor of the distribution of DFS in MDMs and the Integrated Child Development Scheme (ICDS).…”
Section: Introductionmentioning
confidence: 86%
“…This is suggested by findings on the use of iron-fortified salt, another method of low-dose iron supplementation. While the distribution of iron-fortified salt to households in Bihar did not lead to a reduction in anaemia (Banerjee et al, 2018), the distribution to primary schools for use in the school kitchens, also in Bihar, resulted in considerable reductions in anaemia even four years after the start of the intervention (Krämer et al, 2021;von Grafenstein et al, 2021).…”
Section: Introductionmentioning
confidence: 99%